The fundementals of Islam in Kazakh folklore (Eurasian Journal of Philology Science and Education, 2016)
This article discusses an Islam basics in folklore since the VII century. In folklore and written literature of the Turkic countries, Arab peninsulas, Central Asia and Kazakhstan the general sagas of the Koran and legend which are given from the prophet Muhammad’s hadis and also the poems having educational value are analyzed. The article explores fundamentals of Islam as the special section in national Kazakh literature and its safety of heritage for modern generation. In common literature of the Islamic countries the options of works changed by local poets and writers are shown.
Keywords: islam; folklore; The Holy Quran; oral literature.